Behavioral and social science : (National Academy Press, 1986)
In 1933, President Herbert Hoover commissioned the "Ogburn Report," a comprehensive study of social trends in the United States. Fifty years later, a symposium of noted social and behavioural scientists marked the report's anniversary with a book of their own from the Commission on Behavioural and Social Sciences and Education. The 10 chapters presented here relate the developments detailed in the "Ogburn Report" to modern social trends. This book discusses recent major strides in the social and behavioural sciences, including sociology, psychology, anthropology, economics, and linguistics.